2006
DOI: 10.1889/1.2451409
|View full text |Cite
|
Sign up to set email alerts
|

21.4: Development of Low-Retardation TAC FILM for Color-Shift Improvement in LCDs

Abstract: We have developed the birefringence control technology of TAC film by organic additives. By using this technology, for the first time in the world, we could industrialize new TAC film whose Re value (in‐plane retardation) and Rth value (out‐of‐plane retardation) are both nearly zero. This TAC film has very interesting feature that Rth variation is very small even if stretch force is loaded. Therefore, it is proper to make polarizer and attach the polarizer on LCD panel because accidental Rth doesn't rise in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Instead, a low-retardation triacetyl cellulose (TAC) polarizer is used. Th e TAC fi lm has almost no birefringence, and improves the color shift that occurs under diagonal off -axis viewing in the IPS mode [34].…”
Section: Compensation Fi Lms For Va and Ips Modesmentioning
confidence: 95%
“…Instead, a low-retardation triacetyl cellulose (TAC) polarizer is used. Th e TAC fi lm has almost no birefringence, and improves the color shift that occurs under diagonal off -axis viewing in the IPS mode [34].…”
Section: Compensation Fi Lms For Va and Ips Modesmentioning
confidence: 95%
“…For example, TAC film is used today as the polarizer substrate in automotive LCD displays. 4 In lab testing, an LC cell comprising two sheets of 40-micron TAC film enclosing LC material between the two substrates was biaxially thermoformed to a spherical radius of 100 mm and showed no change in performance (Fig. 7).…”
Section: Biaxial Curvature and The Potential Of Thermoformingmentioning
confidence: 99%
“…12,13 Therefore, the regulation of the orientation birefringence of optical films has been investigated intensely. 3,4,9,10,14,15 It has been reported that the orientation birefringence (Δn) of a polymer is determined together by the segmental polarizability and the orientation degree (f) 15−17 Here, Δn 0 denotes the intrinsic birefringence of a polymer. n ̅ , ρ, M and N A are the average refractive index, the density, the relative molecular mass, and the Avogadro's constant, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among various kinds of optical films, cellulose triacetate (CTA) film is widely used as the polarizer protective film and the optical compensation film because of its excellent transparency and heat resistance. As a matter of course, as an optical film, the control of optical retardation of CTA film is essential to make it suitable for multiple application modes . For instance, CTA films are expected to have zero retardation when used as polarizer protective films, while they should have appropriate retardations for the application of optical compensation films. , Meanwhile, with the ever-increasing demands of thinner display panels, thinner CTA films are desired . However, as the intrinsic birefringence of cellulose esters themselves are very small, a thinner thickness would narrow the adjustable scope of optical retardation. , Therefore, the regulation of the orientation birefringence of optical films has been investigated intensely. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation